Emergent Transportation “Platforms” in Latin America: Online Communities and Their Governance Models - Lozano-Paredes, Luis H. (Frontiers in Human Dynamics, 2021)
New models of peer governance are emerging from online communities in the global south. This is visible in an understudied case of ridesharing “platforms” created on social media communities and materializing in Latin American cities. In this article, I investigate these online communities in different cities of Colombia and how they develop peer governance models. Developing organization forms that do not follow the typical structure of firms. In these communities, I study the relationships between members, community managers and the governance rules they create, while illuminating the hierarchies present, the accountability of their administrators and its legitimacy. The emerging literatures on platform cooperativism, platform urbanism and peer governance are used to structure a way to understand this new phenomenon with its “southern” particularities. Moreover, in-person and online qualitative research methods are incorporated to engage with the elusive nature of these structures. This will be one of the first studies engaging with the peer governance dilemmas emerging from online communities in the global south. Including an analysis on what the platform literature and the institutional ecosystem in developing countries can harness from the particularities of these community- platforms as they evolve in these contexts.